Effectiveness of interpretive front-of-pack nutritional labelling schemes on the promotion of healthier food choices - Feteira-Santos, R.; Fernandes, J.; Virgolino, A.; Alarcão, V.; Sena, C.; Vieira, C.; Gregório, M. J.; Nogueira, P.; Costa, A.; Graça, P.; Santos, O. (International Journal of Evidence-Based Healthcare, 2020)
Aims: Interpretive front-of-package nutrition labelling can contribute to healthier food habits. This systematic review aimed to examine the effectiveness of interpretive front-of-package nutrition labelling schemes on consumers’ food choices, namely at the moment of food purchase, and to analyse if this potential front-of-package nutrition labelling's effect varies according to different socioeconomic groups. Methods: Electronic databases (Cochrane Library, PubMed, Scopus, and Web of Science) search was performed to identify peer-reviewed articles describing longitudinal studies evaluating the effect of front-of-package nutrition labelling schemes on consumers’ food choices, according to Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA)-Equity 2012 Extension guidelines. No publication-period or language restrictions were applied. PROGRESS-Plus framework was used to report if and how socioeconomic factors were considered in analyses of front-of-package nutrition labelling-related interventions’ effect. Results: Nine studies were selected for narrative synthesis (seven randomized controlled trials and two cross-over trials). When compared with no-interpretive-label conditions, front-of-package nutrition labelling showed a positive impact for nutritional content understanding, healthiness perception of products, selection of products with better nutritional quality, and purchase intention. However, there is no robust evidence of superiority of a specific front-of-package nutrition labelling scheme's effect, neither on consumers’ understanding of nutritional content nor on food choices. An evaluation of the studies following the PROGRESS-Plus framework revealed that socioecononomic status and education were the most frequently used dimensions, when assessing the effect of interpretative front-of-pack nutrition labels. More evidence is necessary to determine the role of front-of-pack nutrition labels in decreasing inequalities between different population subgroups, namely among the most vulnerable subgroups, on the promotion of healthy food choices. Conclusion: Well controlled longitudinal studies, following a real-world evidence approach, are needed to clarify front-of-package nutrition labelling's impact on consumers’ food choices, namely at purchase points, taking into account the most vulnerable population subgroups, such as those with lower literacy and/or financial resources.